(untitled) (Journal of the College of Education for Women, 2019)
The geomorphological importance of studying the alluvial fan derives from the fact thatin enables us to know the Origin and development of such a phenomenon which cover a vastarea in different regions.This study tackles the geomorphological development of Badra alluvial fan throughknowing the factors of its origin, development, form and their present area, by using theclimate hydrological In formation besides using topographic Maps and changes detection fordifferent years (1973 - 2013) from satellite images